Factors Influencing The 30th SEA Games 2019 Medals Acquisition: Indonesian Case Study - Novrizal Achmad Novan; Nuryadi Nuryadi; Komarudin Komarudin; Lius Risnuwanto; Isti kumalasari (JUARA : Jurnal Olahraga, 2021)
An athlete's achievement is influenced by innate talent, internal motivation, and external factors such as family, coach, facilities, and competition. This study aimed to analyze the factors that influence medals for participating athletes in the 2019 SEA Games. The research method used is a case-control study. The case group was athletes who received medals, and the control group was those who did not win medals. A total of 24 athletes who won medals and 22 athletes who did not win medals were involved in this study purposively. The instrument used in this study was a self-administered questionnaire. Data analysis was conducted by using multiple logistic regressions. The results showed that three factors are influencing the medal acquisition of SEA GAMES athletes in 2019. These factors, including participating in various sports during childhood (OR: 9,7), training facilities (OR: 11), and competition, came into the most influential variable (OR: 12,5). In general, types of competition, match results identification; training methods; and availability of facilities all impact the fighting power of athletes. In conclusion, there needs to be a more role from the sports governing body in meeting the needs of athletes' facilities and diversifying athletes to try and participate in several types of sports before specializing in certain sports.